Presence and development of sarcopenia in the context of selected chronic diseases - a systematic review - Lewandowski, Mikołaj; Kwiatkowska, Zofia; Kurkiewicz, Wojciech; Woźniak, Oskar; Mikulska, Jowita; Wąsik, Joanna; Gryboś, Kacper; Sepioło, Weronika; Kiełbratowska, Julia (Quality in Sport, 2025)
Introduction Sarcopenia, the loss of muscle mass, is common in chronic diseases and contributes to adverse outcomes like frailty, falls, and increased mortality. Recent studies show it also affects pediatric patients, impairing growth and development. Sarcopenia and nutritional status both linked to chronic conditions like cancer, surgery, and gastroenterology, share pathophysiological mechanisms but require different treatments. Aim of the study The aim of this study is to provide a clear understanding of the definitions of sarcopenia and nutritional status, as well as their role in chronic diseases. The authors focused mainly on finding the explore the shared and unique mechanisms that underlie these conditions discuss potential diagnostic approaches review the current therapeutic strategies available for managing these two syndromes. Materials and methods The methodology of the literature search involved using the keywords: , Sarcopenia’’, „muscle mass loss”, „chronic disease”, „nutritional status” and „clinical outcomes”. The search terms were entered into the PubMed database. References include systematic reviews, but also clinical trials, as well as case reports. Conclusion Sarcopenia is a critical factor across various patient groups, contributing to poor health outcomes, including higher morbidity, complications, and mortality. Early identification and intervention through exercise, nutrition, and medical management can significantly mitigate these effects, improving quality of life and recovery outcomes. Comprehensive management strategies are essential, particularly for older adults, individuals with chronic conditions, and surgical patients.